O apagamento do rótico em coda final em produções escritas no ensino fundamental II - Branco, Andréia Aparecida Tomáz Castelo (2020)
The influence of speech on writing is a theme that is frequently discussed by several authors (MARCUSCHI, 2007; AQUINO, 2015; MOLLICA, 2003; GARCIA, 2010). As is well known, naturally the aspects of oral language mix with that of writing, especially when dealing with communicative situations. Based on this, this study aimed to analyze the erasure of the “r” in a coda position in the written productions of students in the 8th grade of elementary school and to apply a didactic intervention in order to promote writing with less spelling deviations, mainly with regard to this erasure. To this end, an action research was developed based on the assumptions of Thiollent (2005), with a view to creating a notebook of activities with exercises that develop the necessary language skills and competences so that students feel able to practice writing with less deviations, more monitored. Thus, the Phonetics and Phonology studies were taken as theoretical basis (CARDOSO, 2009; CRISTÓFARO SILVA, 2009; ENGELBERT, 2012; OLIVEIRA, 1983; ROBERTO, 2016; SEARA, 2011; SILVA, 2002), of Educational Sociolinguistics (BORTONI-RICARDO, 2004, 2005, 2006, 2008; PEDROSA, 2004; ZILLES; FARACO, 2015) and the studies on Syllable (ALVARENGA et al, 1989; ALVARENGA; OLIVEIRA, 1997; BISOL, 2013). The results obtained were that, in the initial production, of a total of 30 productions, 10 had erasure of the “r” in a coda position, with the occurrence of this deviation corresponding to a total of 32 occurrences. In the final production, in turn, 8 productions still present the deviation, however with a smaller number of occurrences, corresponding to 15. Still, there was another deviation in the students' production, which is the overcorrection with the addition of the “r” at the end of verbal forms that did not admit this use, being that in the initial production there were 30 occurrences of this deviation, whereas in the final production there was a reduction of more than 50% of the overcorrection, which corresponds to 14 occurrences. Also, corroborating with other studies, it was found that the Thus, this work contributed significantly to the development of the phonetic-phonological awareness of the research participants, so that they developed a more monitored writing linked to situational communication contexts in which they are inserted, thus meeting the proposed objective.